Financial literacy and cash holdings in Türkiye - Mustafa Recep Bilici; Saygın Çevik (Central Bank Review (CBR), 2023)
This paper examines the effect of financial literacy level on cash holdings in Turkey. Utilizing the Methods of Payment Survey, which includes both financial literacy and cash-related data, we first investigate the fundamentals of financial literacy in Turkey. Based on the performance on financial literacy questions, we categorize respondents into three groups. Subsequently, we analyze how cash holding behavior differs among financial literacy groups. Our results reveal that financially literate respondents tend to hold less cash on hand and store more cash elsewhere. Moreover, card ownership increases through financial literacy and the change in payment behavior of financially literate respondents is more significant during Covid-19 pandemic. The results imply that promoting financial literacy may result in less cash usage at points of sale accompanied by the currency in circulation growth, due to the overwhelming effect of increased non-transactional demand following a positive change in financial literacy level.
Keywords: C50; E41; G53; 330; Financial literacy; Money demand; Cash demand